2004
DOI: 10.1073/pnas.0306407101
|View full text |Cite
|
Sign up to set email alerts
|

T cell repertoire scanning is promoted by dynamic dendritic cell behavior and random T cell motility in the lymph node

Abstract: Dendritic cells (DCs) ingest antigens in peripheral tissues and migrate to lymph nodes where they present MHC class II-bound antigen to CD4 ؉ T cells. We used two-photon microscopy to image the single-cell dynamics of interactions between DCs and T cells within intact lymph nodes in the absence of relevant antigen. DCs were fluorescently labeled in vivo by cutaneous injection of alum adjuvant including carboxyfluorescein diacetate succinimidyl ester (CFSE). CFSE-positive DCs (CD11c ؉ , CD11b ؉ , and low-to-int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
428
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 382 publications
(469 citation statements)
references
References 24 publications
(20 reference statements)
32
428
3
Order By: Relevance
“…This is not unexpected, as several studies have shown that very few Ag-presenting DCs are necessary to induce potent immune responses. 42,43 It is likely that few 'prolonged' antigenbearing DCs can amplify Ag-specific T-cell responses (Figures 2 and 3) in this immunologic compartment. Taken together, these observations indicate that administration of CD11c-Bcl-xl DNA prolongs T-cell stimulation and improves the magnitude of TRP2-specific-CD8+ T-cell response induced by TRP2hsp70 DNA vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not unexpected, as several studies have shown that very few Ag-presenting DCs are necessary to induce potent immune responses. 42,43 It is likely that few 'prolonged' antigenbearing DCs can amplify Ag-specific T-cell responses (Figures 2 and 3) in this immunologic compartment. Taken together, these observations indicate that administration of CD11c-Bcl-xl DNA prolongs T-cell stimulation and improves the magnitude of TRP2-specific-CD8+ T-cell response induced by TRP2hsp70 DNA vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that DCs have extreme efficacy in stimulating T cells in the lymph lodes. 43 A recent study showed that individual long-lasting DC-T-cell interactions result in priming, whereas brief contact may contribute to the induction of T-cell tolerance. 51 It is likely that prolonged antigen-bearing DC survival may increase the chance or stability of DC-T-cell interactions during the induction of T-cell priming.…”
Section: Discussionmentioning
confidence: 99%
“…The direct observation also allows to investigate cell-cell interactions that is especially important when analyzing the function of immune cells (Gunzer 2007). For example, the duration of contacts between T cells and APC (Bousso and Robey 2003;Castellino et al 2006;Gunzer et al 2000Gunzer et al , 2004Mempel et al 2004;Miller et al 2004a;Shakhar et al 2005), cytotoxic cells and their targets (Mempel et al 2006;Stinchcombe et al 2001) or B cells with antigen containing cells have been analyzed (Batista et al 2001;Fleire et al 2006). …”
Section: Analysis Of Cell Migration In Vitromentioning
confidence: 99%
“…Shortly after this, the Wrst papers investigating cell migration in explanted lymph nodes or thymic stromal reaggregate cultures (Bousso et al 2002) were published, followed by true intravital studies (Gunzer et al 2004;Mempel et al 2004). Meanwhile the number of reports using intravital 2PM for immunological questions has risen enormously, spanning from the cellular events of T cell activation (Miller et al 2004a), formation and function of germinal centers (Allen et al 2007b;Schwickert et al 2007) or function of regulatory T cells (Tadokoro et al 2006) to complex processes such as granuloma formation ) and the delivery of antigens (Carrasco and Batista. 2007;Qi et al 2006) or viruses to B cells (Junt et al 2007a).…”
Section: Analysis Of Cell Migration In Vivomentioning
confidence: 99%
“…More recently in vivo documentation of T cell and APC trafficking and interactions have been documented, especially through the use of two photon confocal microscopy [4,5,6,7,8,9]. The majority of these studies involve the lymph node or other lymphoid organ such as the bone marrow or thymus [10,11].…”
Section: Introductionmentioning
confidence: 99%